Word’s and Silence’s Magic in Polish Folk Tale - Wróblewska, Violetta (Poznańskie Studia Slawistyczne, 2012)
The article’s main subject refers to some magical aspects of the literary communication which might be observed in the selected examples of Polish fairy tale, composed in the nineteenth century and at the beginning of the twentieth one. The crucial issue of the article concerns a certain relationship between the magic words’ and the silence’s forms and the folk world outlook which reveals itself as a realm, constituted on a structure of opposition. Moreover, in the paper one may also encounter with a characteristics of the functions of spells, whispers and scenes of silence that appear in the folk tales.